Exegeting the Jews : the early reception of the Johannine Jews - Azar, Michael G. (The Bible in Ancient Christianity, 2016)
In Exegeting the Jews: The Early Reception of the Johannine \'Jews\' , Michael G. Azar analyzes the rhetorical function of the Gospel of John's \'Jews\' in the earliest surviving full-length expositions of John in Greek: Origen's Commentary on John (3rd century), John Chrysostom's Homilies on John (4th century), and Cyril of Alexandria's Commentary on John (5th century). While scholarship often has portrayed the reception history ( Wirkungsgeschichte ) of the Gospel's "Jews" as simply and uniformly anti-Jewish or antisemitic, Azar demonstrates that these three writers primarily read John's narrative typologically, employing the situation and characters in the Gospel not against contemporary Jews with whom they regularly interacted, but as types of each patristic writer's own intra-Christian struggle and opponents.